Emma Dilemma, the nanny, and the best horse ever - Hermes, Patricia (New York : Marshall Cavendish, 2011)
Emma's happy summer of soccer camp with best friend Luisa and visits to Rooney, the beloved old horse at the nearby stables where Annie the nanny helps out, changes when she discovers that Rooney is being sold and Luisa has some unhappy news.
Ages 9-12
Keywords: Horses -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Nannies -- Fiction; Family life -- Fiction; Moving, Household -- Fiction